Inflammation as a chemoprevention target in asbestos-induced malignant mesothelioma. (10th November 2022) - Kadariya, Yuwaraj; Sementino, Eleonora; Shrestha, Ujjawal; Gorman, Greg; White, Jonathan M; Ross, Eric A; Clapper, Margie L; Neamati, Nouri; Miller, Mark Steven; Testa, Joseph R
Abstract: Malignant mesothelioma (MM) is an incurable cancer of the serosal lining that is often caused by exposure to asbestos. Therefore, novel agents for the prevention and treatment of this disease are urgently needed. Asbestos induces the release of pro-inflammatory cytokines such as IL-1β and IL-6, which play a role in MM development. IL-6 is a component of the JAK-STAT3 pathway that contributes to inflammation-associated tumorigenesis. Glycoprotein 130 (gp130), the signal transducer of this signaling axis, is an attractive drug target because of its role in promoting neoplasia via the activation of downstream STAT3 signaling. The anticancer drug, SC144, inhibits the interaction of gp130 with the IL-6 receptor (IL6R), effectively blunting signaling from this inflammatory axis. To test whether the inflammation-related release of IL-6 plays a role in the formation of MM, we evaluated the ability of SC144 to inhibit asbestos-induced carcinogenesis in a mouse model. The ability of sulindac and anakinra, an IL6R antagonist/positive control, to inhibit MM formation in this model was tested in parallel. Asbestos-exposed Nf2 +/− ;Cdkn2a +/− mice treated with SC144, sulindac or anakinra showed significantly prolonged survival compared to asbestos-exposed vehicle-treated mice. STAT3 activity was markedly decreased in MM specimens from SC144-treated mice. Furthermore, SC144 inhibited STAT3 activation by IL-6 in cultured normal mesothelial cells, and in vitro treatment of MM cells with SC144 markedly decreased the expression of STAT3 target genes. The emerging availability of newer, more potent SC144 analogs showing improved pharmacokinetic properties holds promise for future trials, benefitting individuals at high risk of this disease. Abstract : These findings provide a rationale for further exploration of new SC144 analogs as IL-6/JAK-STAT3 pathway inhibitors in individuals at risk of MM due to asbestos-induced inflammation, including workers occupationally exposed to these deadly carcinogenic fibers. Graphical abstract: